PENGEMBANGAN BAHAN AJAR PEMBELAJARAN TEKS LAPORAN HASIL OBSERVASI BERDASARKAN INDEKS KEPADATAN LEKSIKAL PADA KELAS X - Purnamasari, Cici; Marlia, Marlia; Triandy, Rendy (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2024)
This research is motivated by the difficulty of students in understanding teaching materials that have complex sentences. The purpose of this research is to develop class X Indonesian teaching materials, especially chapter 1 of the observation report text based on the lexical density index. The method used is research and development (R&D) with primary data collection techniques from class X Indonesian teaching materials and secondary data from observations, questionnaires, and documentation of class X-5 at Pasundan 3 Bandung High School. This research uses Halliday's theory (1985) to calculate the lexical density index. The results showed that the lexical density index in the original teaching materials was 8.1 (very high). The development of teaching materials was carried out by simplifying the sentences, thus reducing the lexical density index to 6.4 (medium). After developing teaching materials, students understand the teaching materials that have been developed better than the original teaching materials. This is reinforced by the pretest average value of 62.5 and increased with the posttest average value to 81.5. In addition, the questionnaire results showed that 40% of students understood the teaching materials before they were developed and 60% did not understand them, and were also reinforced by the results of the validation of educators who stated that the development version of teaching materials was feasible to use. Thus, the development of teaching materials based on the lexical density index was successful in improving students' learning outcomes.